2013
DOI: 10.1007/s10695-013-9863-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of allostatic load on hypothalamic–pituitary–interrenal (HPI) axis before and after secondary vaccination in Atlantic salmon postsmolts (Salmo salar L.)

Abstract: The experiment consisted of three experimental groups; 1) "vaccine and stress", 2) "stress and vaccine" and 3) control. All groups have previously been vaccinated 6 months prior to the start of the experiment. At the start of the experiment the "vaccine and stress" group was vaccinated with Pentium Forte Plus for the second time (25.02.2008), and then given a daily stressor (crowding stressor, 267 kg m-3 in 15 min) for a period of four weeks. The "stress and vaccine" group was given a similar daily stressor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 80 publications
(107 reference statements)
1
23
0
Order By: Relevance
“…Stress has been linked to increased plasma Mg 2+ concentration over time in anaesthetized rainbow trout (O. mykiss) when MS-222 was used following a stressor (being lifted out of the water for 20 seconds) (Soivio et al, 1977). Similar link between plasma cortisol and Mg 2+ has also been shown in Atlantic salmon following daily crowding stress for 4 weeks with a subsequent vaccination (Iversen and Eliassen, 2014). Iversen and Eliassen concluded that fish who may have entered an allostatic overload type 2 became oversensitive to ACTH, reducing efficient negative feedback system and elevating base-line level of plasma cortisol.…”
Section: Discussionmentioning
confidence: 86%
“…Stress has been linked to increased plasma Mg 2+ concentration over time in anaesthetized rainbow trout (O. mykiss) when MS-222 was used following a stressor (being lifted out of the water for 20 seconds) (Soivio et al, 1977). Similar link between plasma cortisol and Mg 2+ has also been shown in Atlantic salmon following daily crowding stress for 4 weeks with a subsequent vaccination (Iversen and Eliassen, 2014). Iversen and Eliassen concluded that fish who may have entered an allostatic overload type 2 became oversensitive to ACTH, reducing efficient negative feedback system and elevating base-line level of plasma cortisol.…”
Section: Discussionmentioning
confidence: 86%
“…In domesticated mammals, an injection of ACTH has shown an increased cortisol response in animals reared in poor conditions or subjected to repeated stressors. Similarly, Iversen and Eliassen (2014) showed that salmon that were stressed daily over a 4-week period became oversensitive to ACTH, regardless of whether the fish were vaccinated before or after applied stressor. One can only speculate how the Model treatment triggered the HPI axis in a single individual.…”
Section: Discussionmentioning
confidence: 95%
“…To avoid stress during handling, fish were quickly hand netted from the experimental tank to a 30 L tank with 5 mg L –1 of cortisol blocking metomidate (Aquacalm™, Western Chemical Inc, Ferndale, United States). This concentration causes rapid anesthesia and stops further increase of plasma cortisol ( Iversen et al, 2003 ; Iversen and Eliassen, 2014 ). Fish were moved back to their respective tanks after the measurements were done.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers have different important points to consider before applying vaccination: biological species characteristics of cultured objects; the real status of the immune system of objects of cultivation; the production cycle and life cycle of the cultivated species on the fish farm; features of the seasonal diseases in a fish hatchery; technology of fish farming processes; abiotic characteristics of the aquatic environment (distribution and fluctuation of temperature, salinity, etc. ); stressing factors; feeding / nutritional characteristics and monetary benefits [7].…”
Section: Purpose Of the Fulfilled Studymentioning
confidence: 99%